Self-Management of Covid-19 Patients with Commorbid Hypertension: Case Study - Lilis Setyowati; Aprilia Ayu Mawardini; Nur Aini; Ollyvia Freeska Dwi Marta; Erma Wahyu Mashfufa (East Asian Journal of Multidisciplinary Research, 2023)
Most COVID-19-positive patients with comorbidities, especially HT (hypertension), are still being debated. Self-management is very useful for improving the quality of life and changing behavior. This study aimed to determine the self-management experience of COVID-19-positive patients with comorbid hypertension. The method used in this study is qualitative research with a case study approach strategy (case study research), using the nursing process approach, obtained using purposive sampling, interviews, physical assessments, and environmental observation. The results of this study obtained self-management carried out by patients: stress management and lifestyle. Even though self-management has been carried out, they are still exposed to COVID due to age and obesity. Discipline toward self-management prevents the transmission of the virus.